2019
DOI: 10.3390/cancers11030298
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Origin, Metabolic Reprogramming and IL-1β Signaling: Promises and Pitfalls in Lung Cancer

Abstract: Macrophages are tissue-resident cells that act as immune sentinels to maintain tissue integrity, preserve self-tolerance and protect against invading pathogens. Lung macrophages within the distal airways face around 8000–9000 L of air every day and for that reason are continuously exposed to a variety of inhaled particles, allergens or airborne microbes. Chronic exposure to irritant particles can prime macrophages to mediate a smoldering inflammatory response creating a mutagenic environment and favoring cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 285 publications
1
11
0
Order By: Relevance
“…Macrophages M0 may polarized into different types: M1 and M2 [20,21]. Several studies have revealed that macrophages M1 could promote LUAD cells proliferation, invasion and metastasis [22][23][24] and an increased density of macrophages M1 in TME was associated with poor prognosis in LUAD [25,26], which was in accord with the nding in this study. Previous researches demonstrated accumulating memory B cells were strongly correlated with favorable clinical outcomes in various tumors [27].…”
Section: Discussionsupporting
confidence: 90%
“…Macrophages M0 may polarized into different types: M1 and M2 [20,21]. Several studies have revealed that macrophages M1 could promote LUAD cells proliferation, invasion and metastasis [22][23][24] and an increased density of macrophages M1 in TME was associated with poor prognosis in LUAD [25,26], which was in accord with the nding in this study. Previous researches demonstrated accumulating memory B cells were strongly correlated with favorable clinical outcomes in various tumors [27].…”
Section: Discussionsupporting
confidence: 90%
“…These cells are now known as MDSCs, a heterogeneous population of immature myeloid cell. MDSCs are also plastic and respond to microenvironment signals [40][41][42]. MDSCs can differentiate into macrophages, granulocytes and dendritic cells (DCs) in vitro.…”
Section: Marrow-derived Suppressor Cellsmentioning
confidence: 99%
“…It has been reported that the immunosuppressive activity of MDSCs in the tumor microenvironment mainly includes (a) inducing differentiation and expansion of Tregs; (b) inhibiting the polarization of DCs, NKs and macrophages to the M2 phenotype; (c) depriving T cells of essential amino acids; (d) inducing oxidative stress ( Fig. 2) [40][41][42][43]. We mainly reviewed the MDSCs in the tumor growth, angiogenesis, and metastasis of HCC in this context (Table 1) and an increase in immunosuppressive cytokine levels in HCC patients, revealing the potential mechanistic network for immune disorders in HCC patients compared with the normal control group [55].…”
Section: Marrow-derived Suppressor Cellsmentioning
confidence: 99%
“…The size of each subcutaneously transplanted tumor was measured with the Vevo 2100 Imaging Platform (Visual Sonics, Canada). The tumor volume was calculated with the following formula: tumor volume = 0.5 × long diameter × short diameter 2 .…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Non-small cell lung carcinoma (NSCLC) is the most commonly diagnosed cancer and the leading cause of cancerassociated death (1). The prognosis of NSCLC is poor, and the survival rate is only 15% after 5 years because many of these patients ultimately do not respond to chemoradiotherapy, which is associated with unimaginable degree of cellular heterogeneity within a single tumor (2). The heterogeneity of tumor may correlates with cancer stem cells (CSCs) or tumor-initiating cells (TICs) which may be responsible for NSCLC treatment failure which includes local recurrence, distant metastasis, and the limitations of therapeutic agents (3).…”
Section: Introductionmentioning
confidence: 99%